ANALISIS PRIVASI, KEAMANAN DAN KEPERCAYAAN KONSUMEN TERHADAP PEMBELIAN PADA MARKETPLACE LAZADA co.id DI KABUPATEN NGANJUK - Nofita, Lusi; Bawono, Muhammad; Arintowati, Dyan (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine the Analysis of Privacy, Security and Consumer Trust in Purchases on the Lazada co.id Marketplace in Nganjuk Regency. The population in this study are Lazada co.id Marketplace consumers in Nganjuk Regency who have made purchases at Lazada. The data collection method used in this study was a questionnaire (questionnaire) which was distributed to 100 respondents who were selected using purposive sampling. In the study using the SPSS 25 application. Methods in data analysis using Instrument Test, normality test, classical assumption test, multiple linear regression analysis, hypothesis testing and the coefficient of determination (R2). Based on testing on the F test it was concluded that there was a simultaneous effect between Privacy, Security and Trust on Purchase Decisions of Lazada co.id Marketplace and the results of the t test showed that Privacy, Security and Trust had a positive and significant effect on purchasing decisions of Lazada co.id Marketplace.